2012
DOI: 10.4141/cjps2010-006
|View full text |Cite
|
Sign up to set email alerts
|

Screening ofBrassicagermplasm for resistance toPlasmodiophora brassicaepathotypes prevalent in Canada for broadening diversity in clubroot resistance

Abstract: Hasan, M. J., Strelkov, S. E., Howard, R. J. and Rahman, H. 2012. Screening of Brassica germplasm for resistance to Plasmodiophora brassicae pathotypes prevalent in Canada for broadening diversity in clubroot resistance. Can. J. Plant Sci. 92: 501–515. Clubroot disease of crucifers, caused by Plasmodiophora brassicae, poses a threat to the Canadian canola industry, and the development of resistant cultivars is urgently needed. Germplasm resistant to local pathotype(s) is the prime requirement for breeding club… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 57 publications
(26 citation statements)
references
References 38 publications
2
24
0
Order By: Relevance
“…brassicae have been identified in the canola progenitor species B . rapa 11, 12 . This species could be used to broaden the genetic base of clubroot resistance in canola.…”
Section: Introductionmentioning
confidence: 99%
“…brassicae have been identified in the canola progenitor species B . rapa 11, 12 . This species could be used to broaden the genetic base of clubroot resistance in canola.…”
Section: Introductionmentioning
confidence: 99%
“…Among the A and C genome Brassica species, some genotypes or varieties of B. rapa (2n = 20, AA) often possess clubroot resistance (CR) and also exhibit higher levels of resistance than B. oleracea (2n = 18, CC) (Crisp et al 1989, Hasan et al 2012; for reviews, see Piao et al 2009;Rahman et al 2014). On the other hand, Brassica species that contain the B genome, viz.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Brassica species that contain the B genome, viz. diploid species B. nigra (2n = 16, BB) often carry resistance (Hasan et al 2012), however, the amphidiploid species B. juncea (2n = 36, AABB) and B. carinata (2n = 34, BBCC) are mostly susceptible to clubroot disease (Crisp et al 1989;Diederichsen et al 2009;Hasan et al 2012). In B. rapa resistance is found more commonly in European fodder turnip (B. rapa spp.…”
Section: Introductionmentioning
confidence: 99%
“…In case of B. napus, some of the swede or rutabaga (B. napus var. napobrassica) genotypes reported to possess resistance to different P. brassicae pathotypes (Ayers and Lelacheur 1972;Buczacki et al 1975;Crute et al 1983; Gustafsson and Falt 1986) including the pathotypes prevalent in Canada (Hasan et al 2012). Ayers and Lelacheur (1972) reported that resistance to P. brassicae races 2 and 3 in rutabaga cv.…”
mentioning
confidence: 99%
“…Wilhelmsburger carries one gene for resistance to race 3 and two genes for resistance to race 2. Hasan et al (2012) reported that the rutabaga cultivars Brookfield and Polycross carry resistance to pathotypes 2, 3, 5, 6 and 8 which are threats to the Canadian canola crop. The objectives of this research was to study the genetic basis of resistance in Brookfield, and map the resistance genes through construction of a linkage map and identify molecular markers for use in marker assisted selection.…”
mentioning
confidence: 99%